A Critical Overview of Labeling Information of Pomegranate Juice‐Based Drinks: Phytochemicals Content and Health Claims. Issue 4 (18th March 2019) - Cano‐Lamadrid, Marina; Turkiewicz, Igor Piotr; Tkacz, Karolina; Sánchez‐Rodríguez, Lucía; López‐Lluch, David; Wojdyło, Aneta; Sendra, Esther; Carbonell‐Barrachina, Angel A.
Abstract : Abstract: Punicalagin is responsible for over 50% of the antioxidant activity of pomegranate, but ellagic acid (EA) and total polyphenol content (TPC) are also key parameters regarding pomegranate bioactivity. Many juices and other drinks based on pomegranate take advantage from the widespread healthy image of this fruit, whereas their real content of bioactive phytochemicals is low. For that reason, the objective of this study was to compare the labelling information with the real phytochemical contents (TPC, punicalagin [Pn] [isomers α, β ], and EA). Titratable acidity (TA), color density (CD), polymeric color (PC), and sensory profiles (trained panel) were assessed. The experimental ranges of TPC and Pn contents were 2.75 to 70.9 mg/g and traces to 3.18 mg/g, respectively. The percentage of pomegranate juice was highly correlated with the intensity of the pomegranate ID attribute ( R  = 0.85; p <  0.001), Pn content ( R  = 0.71; p <  0.001), and EA content ( R  = 0.36; p <  0.001). The experimental results showed a high variability in the content of bioactive compounds and the need to urge food companies to optimize processes and storage conditions. Although no health claim for pomegranate has been authorized so far at the European Union, significant mismatches among labelling and bioactive compounds content are misleading consumers. Practical Application: Pomegranate juice and nectar producers need to evaluate the real content of bioactive Pn, EA, and TPC in their products to optimize formulation, heat treatment, packaging and storage conditions to guarantee high levels of bioactive compounds during shelf life. Producers' organizations may benefit from harmonizing Pom products labelling, so they may fulfill consumer expectations and may be ready if health claims are finally authorized for these products. The development of a new sensory quality marker will be an interesting option.